Derived hybrid biosorbent for zinc(II) removal from aqueous solution by continuous-flow activated sludge system. (April 2020) - Jagaba, A.H.; Kutty, S.R.M.; Khaw, S.G.; Lai, C.L.; Isa, M.H.; Baloo, L.; Lawal, I.M.; Abubakar, S.; Umaru, I.; Zango, Z.U.
Graphical abstract: Highlights: Groundwater Treatment Plant Sludge exhibited high sorption capacity to Zn(II) ions. The biosorption of Zn(II) ions by Microwave Incinerated Rice husk ash was outstanding. Developed hybrid biosorbent captured Zn(II) ions with high sensitivity and selectivity. Elution studies proved the reusability of biosorbents without significant deterioration. Sludge in all effluents evaluated classified as good quality sludge since SVI < 100 mL/g. Abstract: Zinc ion is a toxic metal mostly contained in industrial effluents. To minimize its contamination levels due to the detrimental effect on both human health, environment and the eco-system, developing novel materials is essential for the removal of zinc ions. This study focused on the development and utilization of groundwater treatment plant sludge, microwave incinerated rice husk ash and derived hybrid biosorbent for the removal of zinc ions from aqueous solution. Standard methods were adopted for the preparation and characterization of the biosorbents and zinc aqueous solution. The biosorption experiments performed in batch systems at room temperature. Factors that may affect the zinc removal efficiency such as pH, reaction time, initial concentration, counter-ions, regeneration studies and substrate removal rate were investigated. Results indicated that the developed biosorbents removed zinc concentration between 84–99 %. Removal efficiencies for derived hybrid biosorbent at different zinc concentrations were in the order 0.5 m/L > 1.0 mg/L > 5.0 mg/L > 2.0 mg/L > 10 mg/L > 15 mg/L. The effluent concentrations were between 0.01–3.52 mg/L, 0.01–1.27 mg/L, 0.01–2.31 mg/L and 0.01–2.01 mg/L for groundwater treatment plant sludge, microwave incinerated rice husk ash and derived hybrid biosorbent respectively. The biosorbents exhibited high affinity to zinc ion in the presence of competing ions. Biosorbents were regenerated into their initial functionality by HCl acid without significant capacity loss. Therefore, the biosorbents can be viable alternatives for efficient zinc removal because they are highly sensitive, selective and sustainable.